Changing Assessment Practices in the Classroom: A Study of One Teacher's Challenge - Lock, Cinde; Munby, Hugh (Alberta Journal of Educational Research, 2000)
This article details the challenges encountered by an elementary schoolteacher as he tried to introduce new assessment practices in his classroom. The case study seeks to identify and describe the factors that influenced this teacher's introduction of portfolios and student conferences in the context of the complexity of student assessment practices. The empirical work for the case study, which was set in the context of a collaborative research program, was conducted over a 12-month period with a grade 7-8 generalist teacher, George, in a small urban school. Several modes of data collection were used in the study: classroom observations, informal discussions, and scheduled interviews. Analysis identified four dominant influences on George's implementation of the new assessment program: (a) his beliefs about the nature of teaching and learning; (b) his understandings about these newer forms of assessment and their influence on his other classroom practices; (c) his involvement in the overall collaborative research program; and (d) the contextual influences of the school environment. The study concludes that, without altering his beliefs about teaching and learning and his teacher-centered instructional practices, George would find it particularly difficult to implement a student centered assessment program in his classroom.